Ответ:
-0.25
Объяснение:
При x = 0, возникает неопределенность вида 0/0. Используем правило Лопиталя.
производная (x-sin2x) = 1 - 2cos(2x)
производная (x+sin3x) = 3cos(3x) + 1
Предел равен (1-2cos(0)) / (3cos(0)+1) = (-1)/(4) = -0.25
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
-0.25
Объяснение:
При x = 0, возникает неопределенность вида 0/0. Используем правило Лопиталя.
производная (x-sin2x) = 1 - 2cos(2x)
производная (x+sin3x) = 3cos(3x) + 1
Предел равен (1-2cos(0)) / (3cos(0)+1) = (-1)/(4) = -0.25